2009
DOI: 10.1159/000209391
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of DNMT1 and DNMT3a in Salivary Gland Neoplasms

Abstract: Objective: Salivary gland neoplasms pathogenesis has not been well established. DNA methylation occurs when methyl groups are added to cytosine nucleotides in specific areas of the gene by the enzyme DNA methyltransferase (DNMT). This chemical modification can alter gene expression without altering DNA sequence. While DNMT3a is mostly involved in de novo methylation, DNMT1 acts as a maintenance methyltransferase. We aimed to investigate the immunoexpression of DNMT3a and DNMT1 in minor salivary gland neoplasms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Few studies have analyzed the expression of DNMTs in MEC. As in the present study, Cavaliéri Gomes et al (2009) 20 also demonstrated that the nuclear expression of DNMT1 and DNMT3A was concentrated in the salivary gland tumors, whereas DNMT3A was predominantly cytoplasmic. The presence of DNMT3A and DNMT3B is associated with novel methylation in the DNA 21 .…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have analyzed the expression of DNMTs in MEC. As in the present study, Cavaliéri Gomes et al (2009) 20 also demonstrated that the nuclear expression of DNMT1 and DNMT3A was concentrated in the salivary gland tumors, whereas DNMT3A was predominantly cytoplasmic. The presence of DNMT3A and DNMT3B is associated with novel methylation in the DNA 21 .…”
Section: Discussionsupporting
confidence: 88%
“…To date, information about the expression of DNMT3A in SGTs remains scarce. A single study has shown that in minor SGTs, DNMT3A shows mainly nucleic distribution and that nuclear immunohistochemical staining is observed in almost 17% of ACCs [64].…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate with our findings, suggesting a hypermethylated profile in different oral pathologies. On the other hand, some studies have found that DNMT1 expression was similar among normal salivary gland tissue and benign and malignant salivary gland tumors [34,35]. However, Shieh et al found that mucoepidermoid carcinoma (MEC) without DNMT1 expression had longer survival rates than MEC patients with DNMT1 immunoreactivity (mean 71.9 and 31.9 months, respectively) [35].…”
Section: Discussionmentioning
confidence: 99%